Persistent Challenges in Cross Cultural Quantitative Research: Measuring Classroom Dynamics in Adult Learning in Ireland and the USA - Máirtín Ó Fathaigh; Thomas Valentine (Adult Education Research Conference, 2005)
This research roundtable will explore some of the conceptual and methodological considerations that underpin high-quality cross-cultural quantitative research. The core problem to be addressed can be best exemplified by real-world vignettes drawn from our own experiences.